2007
DOI: 10.1300/j457v03n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Use by Older Adults Knocking on the Door of the Nursing Facility

Abstract: Since 1983, federal funding has been available for hospice services. However, research studies have found that hospice is underutilized by people with terminal illnesses and their families. Low-income older adults are particularly at risk for underutilization. This study examined utilization of hospice services by nursing home applicants in one Midwestern state. Characteristics of users and non-users, and potential barriers to hospice use were examined. Findings further document that hospice is underutilized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…A recent study found that, even when procedures were in place to systematically assess whether new nursing home residents would benefit from outside resources, residents eligible for hospice services were often not referred to hospice. 16 Lack of knowledge of hospice benefits, on the part of both nursing home staff and residents’ family members, was identified as a barrier to hospice referral. Other research has shown that family members find late hospice referrals (or no hospice referral) to be problematic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study found that, even when procedures were in place to systematically assess whether new nursing home residents would benefit from outside resources, residents eligible for hospice services were often not referred to hospice. 16 Lack of knowledge of hospice benefits, on the part of both nursing home staff and residents’ family members, was identified as a barrier to hospice referral. Other research has shown that family members find late hospice referrals (or no hospice referral) to be problematic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Older people have disproportionately less access to hospice and community palliative care services (Catt et al, 2005;Chapin et al, 2007). However, the Longitudinal Study Amsterdam (Klinkenberg et al, 2005) found that significantly more older people dying of cancer were able to stay at home than those dying of other causes.…”
Section: Preferred Place Of Carementioning
confidence: 99%
“…[7][8][9] The hospice field mirrors the disparities in the health care system as a whole, with African American patients underutilizing hospice services. 2,10,11 Although the US Census Bureau estimated that African Americans comprised 13% of the US population in 2013, 12 the National Hospice and Palliative Care Organization (NHPCO) reported that in 2013, only 8.4% of hospice patients identified themselves as African American. This number had decreased from 8.6% the year before.…”
Section: Introductionmentioning
confidence: 99%